2021
DOI: 10.3389/fphy.2021.715996
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Variable Speed on Collective Movement of Animal Groups

Abstract: The collective dynamics and structure of animal groups has attracted the attention of scientists across a broad range of fields. A variety of agent-based models have been developed to help understand the emergence of coordinated collective behavior from simple interaction rules. A common, simplifying assumption of such collective movement models, is that individual agents move with a constant speed. In this work we critically re-asses this assumption. First, we discuss experimental data showcasing the omnipres… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 58 publications
1
21
1
Order By: Relevance
“…Recent advances in living active matter have found that modifications in individual behaviour through the sensing of local densities lead to the formation of regions of orientational disorder and aggregations [52][53][54][55]. Simiobservations are made in experiments with active colloidal systems employing different methods to program the particle motion, like optical feedback loops and field modulations [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in living active matter have found that modifications in individual behaviour through the sensing of local densities lead to the formation of regions of orientational disorder and aggregations [52][53][54][55]. Simiobservations are made in experiments with active colloidal systems employing different methods to program the particle motion, like optical feedback loops and field modulations [55][56][57].…”
Section: Discussionmentioning
confidence: 99%
“…H. rhodostomus displays a "burst-andcoast" mode of swimming characterized by sequences of sudden accelerations called "kicks" followed by a quasi-passive deceleration period during which the fish glides along a near straight line until the next kick. Consecutive kicks of a single fish do not necessarily have the same length, the same duration, nor the same speed [61]. When swimming in groups, kicks of different fish are asynchronous and of different length, duration and speed.…”
Section: Computational Modelmentioning
confidence: 99%
“…However, unlike Ballerini et al [ 24 ], who propose that birds interact with a fixed number of nearest neighbours, we assume that organisms may randomly choose any k of the K (≥ k ) nearest neighbours; we show this randomness plays an important role in maintaining group cohesion. We also assume that individuals move at variable speeds [ 16 , 34 36 ] and update their motion asynchronously [ 29 , 30 , 37 ], in line with many recent empirical studies [ 16 , 18 , 27 , 32 ]. We reiterate that, in order to show generality of our conclusions, we also study variations of parameter values as well as variations of the model, including a minimal model that has substantially reduced number of parameters.…”
Section: Model and Simulationmentioning
confidence: 99%